The Comparative Method in Biology and the Essentialist Trap - Martinez, Pedro (Frontiers in Ecology and Evolution, 2018)
The comparative method is at the centre of a complex view of biology, according to which organisms are seen as historical products. This is a dynamic view of nature, where genotypes and phenotypes change over evolutionary time under the influence of natural selection. Organisms (species) and groups of them (clades) are defined by their uniqueness, and their comparison provides insight into patterns of diversification. The alternative, mechanistic approach is enormously powerful, and has led to our understanding of basic molecular mechanisms underlying biological processes. However, because of intrinsic practical difficulties, this latter approach has only been applied to a very small cohort of animal systems, the so-called “model systems”. While this approach has been enormously productive, it has brought with it as a by-product a narrow view of biological diversity; and the assumption that with just a handful of well-studied animals we “understand” development and evolution. Nothing could be further from the truth, as indicated by many recent studies, which have shown that the development of animals is highly plastic. The lack of appreciation of this simple fact has brought me (and others) to see the field of developmental biology as caught within an “essentialist trap” from which many contemporary evo-devo approaches try to free it.